Faldaprevir combined with peginterferon alfa‐2a and ribavirin in chronic hepatitis C virus genotype‐1 patients with prior nonresponse: SILEN‐C2 trial12. Issue 6 (12th June 2013) - Sulkowski, Mark S.; Bourlière, Marc; Bronowicki, Jean‐Pierre; Asselah, Tarik; Pawlotsky, Jean‐Michel; Shafran, Stephen D.; Pol, Stanislas; Mauss, Stefan; Larrey, Dominique; Datsenko, Yakov; Stern, Jerry O.; Kukolj, George; et al.
Abstract Faldaprevir (BI 201335) is a potent, hepatitis C virus (HCV) NS3/4A protease inhibitor. In all, 290 noncirrhotic HCV genotype (GT)‐1 patients with prior null (<1 log10 viral load [VL] drop at any time on treatment) or partial response (≥1 log10 VL drop but never undetectable on treatment) were randomized 2:1:1 to receive 48 weeks of peginterferon alfa‐2a and ribavirin (PegIFN/RBV) in combination with faldaprevir 240 mg once daily (QD) with 3 days PegIFN/RBV lead‐in (LI), 240 mg QD without LI, or 240 mg twice daily (BID) with LI. Patients in the 240 mg QD/LI group achieving maintained rapid virologic response (mRVR; VL <25 IU/mL [Roche TaqMan] at week 4 and undetectable at weeks 8 to 20) were rerandomized to cease all treatment at week 24 or continue PegIFN/RBV up to week 48. Sustained virologic response (SVR) rates were 32%, 50%, and 42% in prior partial responders, and 21%, 35%, and 29% in prior null responders in the faldaprevir 240 mg QD/LI, 240 mg QD, and 240 mg BID/LI groups, respectively. In the 240 mg QD/LI group, a significantly higher proportion of mRVR patients rerandomized to 48 weeks' treatment achieved SVR compared with those assigned to 24 weeks treatment (72% versus 43%; P = 0.035). Rates of gastrointestinal disorders, jaundice, dry skin, and photosensitivity were increased at 240 mg BID compared with the 240 mg QD dose. Faldaprevir discontinuations owing to adverse events occurred in 6%, 4%, and 23% of patients in the 240 mg QD/LI, 240 mg QD, and 240 mg BID/LI groups, respectively. Conclusion: Faldaprevir 240 mg QD with PegIFN/RBV was safe and tolerable and produced substantial SVR rates in prior null and partial responders. The 240 mg QD dose is currently undergoing phase 3 evaluation. (Hepatology 2013;57:2155–2163)